2019
DOI: 10.1093/advances/nmz007
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a Paleolithic Diet on Cardiovascular Disease Risk Factors: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: There is some evidence supporting the beneficial effects of a Paleolithic diet (PD) on cardiovascular disease (CVD) risk factors. This diet advises consuming lean meat, fish, vegetables, fruits, and nuts and avoiding intake of grains, dairy products, processed foods, and added sugar and salt. This study was performed to assess the effects of a PD on CVD risk factors including anthropometric indexes, lipid profile, blood pressure, and inflammatory markers using data from randomized controlled trials. A comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 80 publications
4
58
1
2
Order By: Relevance
“…Males in the PD-EX group retained more lean mass than males in the PD group [ 42 ]. The previous meta-analysis conducted by Ghaedi et al [ 75 ] indicated that the Paleolithic diet (eight RCTs) could significantly decrease anthropometric indexes, including BM, WC, BMI, and FM %. These results were also confirmed by Manheimer [ 76 ], who pointed out that Paleolithic nutrition was more effective in reducing body weight in comparison to the control diet [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Males in the PD-EX group retained more lean mass than males in the PD group [ 42 ]. The previous meta-analysis conducted by Ghaedi et al [ 75 ] indicated that the Paleolithic diet (eight RCTs) could significantly decrease anthropometric indexes, including BM, WC, BMI, and FM %. These results were also confirmed by Manheimer [ 76 ], who pointed out that Paleolithic nutrition was more effective in reducing body weight in comparison to the control diet [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these diseases are caused by environmental factors, with the diet being one of the main contributing factors. While the consumption of highly processed foods and sugar-sweetened beverages has been associated with a higher risk of these disorders, a healthy diet including functional foods may help in reducing or even preventing several NCDs [ 1 , 2 ]. Thus, in recent years, the search for bioactive food compounds and their use as substitutes of pharmacological treatments has intensified.…”
Section: Introductionmentioning
confidence: 99%
“…The diet is based on eating foods available to hunter-gatherer humans before the advent of agriculture. Overall, except for a potential deficiency in Ca due to the exclusion of dairy products, the diet is considered by experts to be healthy (31)(32)(33) . The wide variety of foods (including energy-dense foods) that can be eaten on the Paleo diet may explain the low dropout rate during the winter holiday season and the long compliance time among NJD (34,35) .…”
Section: Discussionmentioning
confidence: 99%